Antecedents of organizational creativity: drivers, barriers or both? - Annika Blomberg; Tomi Kallio; Heikki Pohjanpää (Portugal, 2022)
This paper reviews academic journal articles and scholarly books focusing on organizational creativity and constructs a schematic representation of the antecedents of organizational creativity, i.e. of the associated drivers and barriers. The literature on organizational creativity is reviewed using a traditional review technique. The focus is especially on more recent developments of the discourse, and therefore this work can be labeled as a stateof-the-art review. The review shows that drivers have clearly been studied more extensively than barriers. It was also recognized that the predominant approach among organizational creativity scholars is to dichotomize the factors influencing organizational creativity, more specifically to discuss the antecedents of creativity mostly from the viewpoint of drivers. In some cases, the antecedents are discussed from the perspective of barriers, but only rarely has it been recognized that the very same factor may either enhance or inhibit creativity. In this paper, such factors are called ‘either-or factors’. The paper suggests that the organizational creativity discourse should acknowledge that it is not enough to understand what enhances organizational creativity but also which kind of issues inhibit it and, especially, which factors may work either against or toward creativity under different circumstances. The review suggests that the majority of factors are most likely either-or by nature, although it has been overlooked in the discourse due to the dichotomizing tendency.